The Effect of Tax Collection, Tax Audit, and Taxpayer Compliance on Tax Revenue at the Primary Tax Service Office in Manado - TENDEAN, Geneva Z. O.; PANGERAPAN, Sonny; SARDJONO, Olivia Y. M. (PT Keberlanjutan Strategis Indonesia, 2023)
This study aims to determine the effect of tax collection, tax audit, and taxpayer compliance on tax revenue at the Primary Tax Service Office in Manado for 2018-2022. Tax collection is measured by the number of Tax Collection Letters (STP) for corporate taxpayers, tax audits are measured by the number of Notice of Tax Assessments (SKP) for corporate taxpayers, and taxpayer compliance is measured by the ratio of the number of corporate tax returns received divided by the number of corporate taxpayers at the Manado Primary Tax Service Office. This type of research is quantitative research using secondary data. The sampling technique used was total sampling, and resulted in 60 research samples. The data analysis technique in this study is multiple linear regression using the SPSS 26 program. The results showed that tax collection does not affect tax revenue, tax audits positively affect tax revenue, and taxpayer compliance positively affects tax revenue.